Changes in the oxidative stress biomarkers in liver of streptozotocin-diabetic rats treated with combretum lanceolatum flowers extract - Dechandt, Carlos Roberto Porto; Souza, Damiana Luiza Pereira; Siqueira, Juliany Torres; Pereira, Mayara Peron; Assis, Renata Pires de [UNESP]; Silva, Virginia Claudia da; Sousa Junior, Paulo Teixeira de; Brunetti, Iguatemy Lourenço [UNESP]; Andrade, Claudia Marlise; Kawashita, Nair Honda; Baviera, Amanda Martins [UNESP] (Sciencedomain International, 2014)
Aims: The study investigated the in vivo antioxidant activity and the in vitro radical scavenging capacity of the Combretum lanceolatum Pohl (Combretaceae) flowers ethanolic extract (ClEtOH) in streptozotocin-diabetic rats. Place and Duration of Study: Department of Chemistry, Federal University of Mato Grosso, Cuiabá, Brazil; between February 2012 and December 2012. Methodology: Male Wistar rats were divided into four groups: Normal rats treated with water/vehicle (N); diabetic rats treated with water (DC); diabetic rats treated with 250 mg/kg (DT250) or with 500mg/kg (DT500) of ClEtOH. After 21 days of treatment, liver samples were used for the analysis of the oxidative stress biomarkers and activity of antioxidant enzymes. In vitro radical scavenger capacity was investigated by the following methods: DPPH radical scavenging, ABTS radical cation decolorization and crocin bleaching assays. Results: Significant oxidative stress was observed in liver of DC, since the malondialdehyde (MDA, biomarker of lipoperoxidation) levels were increased in comparison with N. Increased activities of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were also observed in DC, which could represent a compensatory mechanism against oxidative stress. Glutathione (GSH) levels were lower and similar between N and DC. The MDA levels were significantly decreased in liver of rats from DT250 and DT500, reaching levels similar those of N, suggesting that ClEtOH prevented lipoperoxidation. The treatment of diabetic rats with ClEtOH also increased the GSH levels, as well as increased the GSH-Px activity, and did not change the SOD activity. The results of in vitro radical scavenging capacity indicated that ClEtOH is highly active. Conclusion: These findings indicate that ClEtOH has antioxidant properties in liver of diabetic rats, decreasing lipoperoxidation and increasing the endogenous antioxidant responses. Both the antihyperglycemic effect and the capacity to scavenge free radicals may be related to the antioxidant activity of ClEtOH in diabetes.
Keywords: Combretum lanceolatum Pohl; Streptozotocin-diabetic rats; Malondialdehyde; Reduced glutathione; Antioxidant enzymes